Fisiotareapia En La Clinica Equina (2024)
Animal welfare is a growing concern in our society, where the goal is to keep animals in an optimal state both in their environment and in their current and future treatments. In this context, physiotherapy and rehabilitation emerge as evidence-based disciplines, with the main objective of reinforcing, maintaining and preventing injuries in animal patients.